Full paying patient service in public hospital: An overview. - Malindawati, Mohd Fadzil; Sharifa Ezat, Wan Puteh; Azimatun, Noor Aizuddin; Zafar, Ahmed (Malaysian Public Health Physicians’ Association, 2021)
Globally, the expansion of private health sectors has caused movement of specialists from the public to private sector, causing a disproportionate manpower distribution between the public and private health sector. Retention of clinical specialists in the public sector has become a major problem in Malaysia. The pressure of increasing economic burden, scarce financial resources and increasing rate of medical specialist attrition to the private sector have led the Malaysian Government to introduce Full Paying Patient (FPP) Service as the Ministry of Health Malaysia (MOH) specialists’ retention scheme in 2007. These initiatives have raised the level of payments to public sector doctors. Literature review of MOH documents and secondary data analysis was carried out to provide an overview and better understanding of FPP services implementation practices in MOH hospitals. Findings show the progress in MOH FPP Services’ governance and service operation for achieving the service objectives and noticed an increase in the understanding of the complexities involved in implementing FPP service. As of the end of December 2020, there are 11 public hospitals implementing FPP Service. By December 2018, there were 360 registered FPP Specialists compared to 71 FPP Specialists in the year 2009. The 26,739 patients who opted for this service in 2018 contributed to more than RM22 Million revenue in 2018. Thus, the establishment and operation of FPP Service has brought a considerable number of specialist retention, contributing to the government revenue, indirectly reducing the government subsidy for patients who can afford to pay, and giving patients alternatives in health service options at public hospitals.